2020
DOI: 10.21037/atm.2020.01.63
|View full text |Cite
|
Sign up to set email alerts
|

Pathological myopia-induced antioxidative proteins in the vitreous humor

Abstract: Background: This study aimed to investigate differentially expressed proteins in the vitreous humor (VH) of pathological myopia (PM) and normal eyes.Methods: VH samples were collected from patients undergoing surgical treatment for rhegmatogenous retinal detachment (RRD), idiopathic epiretinal membrane (ERM), myopic retinoschisis (MRS) or macular hole (MH). A label-free quantitative proteomic analysis was performed to detect the differentially expressed proteins, and expression of three differentially expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Along the same lines, the inhibition of certain mitochondrial pathways mediated by oxidative stress preserves photoreceptors after retinal detachment [ 39 ]. This would be particularly important in the case of highly myopic eyes due to the impaired oxidative stress situation in the eyes of these patients [ 28 , 40 , 41 ] where it has also been reported that there is a decrease in the antioxidant proteins in the vitreous humor of pathological myopia patients undergoing retinal surgical treatment (among others for rhegmatogenous retinal detachment) compared with in controls [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Along the same lines, the inhibition of certain mitochondrial pathways mediated by oxidative stress preserves photoreceptors after retinal detachment [ 39 ]. This would be particularly important in the case of highly myopic eyes due to the impaired oxidative stress situation in the eyes of these patients [ 28 , 40 , 41 ] where it has also been reported that there is a decrease in the antioxidant proteins in the vitreous humor of pathological myopia patients undergoing retinal surgical treatment (among others for rhegmatogenous retinal detachment) compared with in controls [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…VH seems to be the best, relatively less invasively accessible surrogate material for research on human chorioretinal omics. In a study conducted by Wei et al [10], patients subjected to PPV were classified based on the lack of PM signs (AL < 26.5 mm), presence thereof (26.5 mm < AL <29.0 mm) or occurrence of high PM (>29.0 mm), and then subdivided according to a specific pathology: MH, ERM, RRD or MRS. Expression of prostaglandin-H2 D-isomerase (PGDS) and glutathione peroxidase 3 (GPX3) in the PM groups was shown to be significantly lower than in the controls.…”
Section: Proteomicsmentioning
confidence: 99%
“…The evidence from in vitro studies suggests that L-PGDS can potentially prevent oxidative stress and apoptosis-related neurodegenerative diseases. In turn, GPX3 is known to catalyze the reduction of organic hydroperoxides and hydrogen peroxide (H 2 O 2 ) to protect cells from oxidative damage [10].…”
Section: Proteomicsmentioning
confidence: 99%
See 2 more Smart Citations